PERANAN STAKEHOLDER TERHADAP PERENCANAAN PEMBANGUNAN DI KELURAHAN MASSEPE KECAMATAN TELLU LIMPOE KABUPATEN SIDENRENG RAPPANG - Rohandi Rohandi (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
Target of this research is to know Role of Stakeholder in the plan Development in Sub-District Of Massepe District Of Tellu Limpoe Sub-Province of Sidenreng Rappang and to know factors what influencing role of stakeholder in the plan development in Sub-District Of Massepe District Of Tellu Limpoe Sub-Province of Sidenreng Rappang. Method Research which is used in this research is research method qualitative (tables of percentage). Technics of data collecting namely by alloting quesioner to responder amounting to 33 people. and direct interview to informan amounting to 3 people. Of this research earn explain that Role of Stakeholder in the plan Development in Sub-District Of Massepe District Of Tellu Limpoe Sub-Province of Sidenreng Rappang consist of 3 indicator, that is subsistem taker of policy, 69,75 % with good category, Giver of Service, 72,75% with good category, and receiver affect 75,75% with good category. Result of summary of role of stakeholder show 72,75% with good category. In this research there are factors having an effect on to role of Stakeholder in the plan Development in Sub-District Of Massepe District Of Tellu Limpoe Sub-Province of Sidenreng Rappang that is urgency storey;level 46,25% with good enough category, knowledge 69,75% with good category, Contiguity (communication) 85,5% with good category, and attitude of stakeholder 65 % with good category . Result of factors summary having an effect on to role of Stakeholder in the plan Development show 66,63% with good category